(untitled) (International Journal of Food and Nutritional Sciences, 2022)
India’s rural development and poverty alleviation policy has been anchored on the Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA), which aims to provide guaranteed employment to the rural for at least hundred days to the adults who are willing to do unskilled manual work. Mahatma Gandhi National Rural Employment Guarantee Scheme (MGNREGS) under the act, has been successful in making many changes in the rural landscape of the country. The impact can be felt in education, migration, women empowerment, social behaviour etc. This research focuses on the impact of MGNREGA on migration trends in Ganjam district, Odisha. Through a combination of quantitative analysis and qualitative fieldwork, the study evaluates the effectiveness of MGNREGA in reducing rural-to-urban migration. Findings reveal shifts in migration patterns, factors influencing migration decisions, and the perceived role of MGNREGA in enhancing livelihoods. The paper discusses challenges in implementation and offers policy recommendations to strengthen MGNREGA’s role in curbing migration and promoting sustainable rural development.